THE POET AS PUBLIC INTELLECTUAL: TONY HARRISON'S WAR POETRY. Issue 5 (3rd September 2022) - Handley, Agata
ABSTRACT: The poet Tony Harrison has created work for the stage and television, and even assumed the role of poet/journalist, writing newspaper reports in verse from war-torn Bosnia. His work is underpinned by a belief in the political nature of the act of writing. He has generally attracted a non-working-class readership; nevertheless, he has never abandoned his quest for a 'democratic' poetry. Much of his work has taken the form of a poetry of immediate response to current events. He has also been insistent, at times, on where his poetry should be published. When he wrote 'Initial Illumination' for The Guardian, for example, he argued it should not appear in the 'literary' section, but on the news pages. Harrison sees himself as a 'war poet. He uses his position as a public intellectual to engage in a struggle against dominant discourses and ways of seeing and to bring audiences to confront the horror of war. The article focuses in particular on his Gulf War poem, 'A Cold Coming', in which he uses strategies such as ekphrasis, to position the reader as a kind of 'secondary witness' of a war that had been turned by the media into a distant, anaesthetised spectacle.